IMPROVEMENT OF STUDENT ACHIEVEMENT THROUGH PROBLEM-BASED LEARNING SYSTEM WITH A DIFFERENTIATED APPROACH: OBJECT-ORIENTED PROGRAMMING SUBJECT - Wahyudin Wahyudin; Dwi Fitria Al Husaeni; R. Rasim; Khyrina Airin Fariza Abu Samah; Shah Nazir (Universitas Citra Bangsa, 2026)
The quality of education can determine a country's success in facing the industrial revolution 4.0. Learning innovation towards a new paradigm is expected to be able to solve problems entering the era of Industrial Revolution 4.0. Therefore, this research creates a learning innovation that aims to improve student learning outcomes, especially in object-oriented programming material using a problem-based learning system with a differentiated learning approach. Quantitative research methods with a quasi-experimental design in the form of a non-equivalent pretest-posttest control group design were used in this research. The research subjects were 71 students in class X vocational school majoring in software engineering at SMKN 1 Cimahi, Indonesia. This research focuses on improving learning outcomes for object-oriented programming. The research results show that the abilities of students who use a problem-based learning system with a differentiated approach are more even and higher. Using a differentiated learning approach in problem-based learning is more effective in improving student learning outcomes in object-oriented programming material, compared to just using a problem-based learning model. It is hoped that this research can become a reference to improve the quality of learning to prepare students to face the era of industrial revolution 4.0.